Pembuatan alat ukur kedalaman air menggunakan sensor sonar (An instrument to measure the water depth using a sonar sensor) - Citra Syefriana; - Yohandri (PILLAR OF PHYSICS, 2020)
Technological developments in various fields encourage humans to apply technology, including in fields related to water. The community uses the river as one of the infrastructure of water transportation, tourism, fisheries and trade. So that the depth of the waters is one of the important factors in the activities of the population, especially in relation to river utilization. a sensor that can detect water depth is a sonar sensor using Aquino as a micro controller sends via the HC-05 Bluetooth module and displays on Android via Bluetooth after installing an electronic Bluetooth application. This research is a study that explains the design and performance specifications. Design specifications explain the accuracy and distance accuracy, while performance specifications explain the performance of measuring instruments. The measurement technique used is direct and indirect measurement. Direct measurements carry out by comparing data using standard gauges and water depth meters. Whereas indirect measurement by analyzing the accuracy and accuracy of distance. Based on the results of the research that has been done of the accuracy, an obtained fairly good distance with an average percentage of 99,37% relative accuracy, an average relative error of 0,63%. The accuracy of the distance was taken 118 cm to, in the largest relative error percentage of 0,42% and an average accuracy of 99,58%. While The accuracy of the distance was taken 206 cm to, in the largest relative error of 0,97% and an average accuracy of 99,61%.